Administrative Management Practices and Service Delivery in Selected Non-Governmental Organizations in Kabale District: A Case Study of Kabale Municipality - Barnabas, Nabaasa (Kabale University, 2022)
A Dissertation submitted to Faculty of Economics and Management Sciences in Partial Fulfilment of the Requirements for Award of Master of Arts in Project Planning and Management of Kabale University